Revolutionary act Engines Contemporary Sociological Inductive Study - Zuhir Al Rawashdeh, Alaa; Rebhi Al Arab, Asma; ALawemer, Waleed; Siraj Eldeen F. Ahmed, Osman (International Journal of Psychosocial Rehabilitation, 2020)
The study tries to identify and extrapolate the opinions of Plato, Aristotle, and Ibn Khaldun on the popular revolutions in order to identify the similarities and differences between their theories and ideas and compare this with the causes, engines, goals, and results of the Arab Spring revolutions in order to draw lessons from the ideas of these three thinkers. About the popular revolutions. The study also tried to analyze the reality of the Arab Spring revolutions to look forward to their future through the ideas of Plato, Aristotle, and Ibn Khaldun. The study found that the economic and social causes that lead to popular revolts against the ruling regimes, which Ibn Khaldun spoke of, were closer to the causes of the Arab Spring revolutions than those of Plato and Aristotle were. With regard to the objectives of the revolution, we note that the views and ideas of the three intellectuals have been very much in keeping with the objectives of the Arab Spring revolutions, especially the main goal of the regime’s indifference. With regard to the results of the revolutions, the researchers noted that there is a great similarity between the results of the Arab Spring revolutions and the results reported by Plato, Aristotle, and Ibn Khaldun.